Cooperative learning in higher education: training in social skills of work in group - Clemente Lobato Fraile; Nagore Guerra Bilbao; Pedro Apodaca Urquijo (INFAD, 2015)
Cooperative Learning seems to be the right methodology to tackle the development of the teamwork competence inside the process of teaching-learning at the University. The experience was developed in six different groups which add up as 185 students of different faculties and schools of the University of the Basque Country (UPV/EHU). The outcome of that experience was analyzed by means of a questionnaire which gathers the main competences of teamwork.  The analysis of the dimensions of the questionnaire shows a structure with two dimensions: a. ‘Interpersonal competences’, b. ‘Instrumental competences’. This structure is conceptually coherent and empirically consistent. Results also show significant differences between both dimensions which may be stating the discriminative power of this dimensional structure.